ТЕМАТИКА И ПОЭТИКА АЛЬБОМА ВИКТОРА ЦОЯ «45» - Абдиров, А.М. (SCIENCE and SOCIETY, 2025)
This article examines the thematic and poetic features of Viktor Tsoi's debut album “45” (1982) with the band Kino. The analysis focuses on key themes such as youth alienation, everyday life in late Soviet society, the pursuit of freedom, and romantic innocence. Special attention is given to poetic devices including metaphor, irony, repetition, simplicity of language, and symbolism. The study demonstrates how Tsoi employs everyday imagery and allegory to express social protest and personal experiences. The album “45” is presented as a significant milestone in the development of Tsoi's authorial style and his influence on Soviet rock culture.
Keywords: Viktor Tsoi; album “45”; Soviet rock music; poetics; social criticism; metaphor; youth culture